Global infrastructure and production division by heterogeneous firms - Xu, Daming; Kobayashi, Kiyoshi; Matsushima, Kakuya; Hasan, Sharina Farihah; Segi, Shunsuke (Routledge, 2018)
The authors developed a pure theoretical economic model to discuss the economy-wide welfare implications of the shifts in production locations of multinational firms. The chapter formulates a model based on the Ricardian trade theory of comparative advantage, where firms decide the production location according to labor productivity, wage and their production technology. The constructed model illustrates how reduced cross-border cost facilitates the global division of labor as well as improves the welfare of every country under foreign direct investment. It theoretically shows the value of facilitating cross-border supply chains in terms of regional development.